2020
DOI: 10.22201/ia.01851101p.2020.56.02.07
|View full text |Cite
|
Sign up to set email alerts
|

An Astrometric and Photometric Study of the Intermediate-Age Open Cluster NGC 2158 and Its Eclipsing Binary [Nbn2015]78

Abstract: We present a photometric and astrometric analysis of the NGC 2158 cluster using Gaia DR2 and 2MASS data. The cluster age, color excess, intrinsic distance modulus and distance are calculated to be t = 2.240 ± 0.260 Gyr, E(B − V) = 0.420 ± 0.050 mag, (m − M)⨀ = 12.540 ± 0.130 mag and d⨀ = 3224 ± 200 pc respectively. The photometric analysis and light curve modelling of the proposed eclipsing binary member [NBN2015]78 is performed using the latest version of the Wilson-Devinney (W-D) code. The solutions show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In total, 71/31 member stars of 12/10 OCs 9 are found for the APO-/LM-LRGB samples through crossmatching with the catalog of C18, with further clipping of a few outliers by using line-of-sight velocity and metallicity estimated from APOGEE and LAMOST. Comparisons of our distances of OCs with those published in the literature (e.g., Piatti et al 2003;Bragaglia et al 2006;Carraro et al 2010;Lim et al 2014;Çakmak et al 2020;Abdelaziz et al 2020;Dias et al 2021) are shown in Figure 9 and Table 3. Our distances of OCs agree very well with those distances determined previously, with a negligible median offset of the relative differences in distance ΔD/D of −0.8%/−0.6% and a standard deviation value of 5.6%/3.4% for the APO/LM-LRGB samples.…”
Section: Validation Of Distance Estimatesmentioning
confidence: 74%
“…In total, 71/31 member stars of 12/10 OCs 9 are found for the APO-/LM-LRGB samples through crossmatching with the catalog of C18, with further clipping of a few outliers by using line-of-sight velocity and metallicity estimated from APOGEE and LAMOST. Comparisons of our distances of OCs with those published in the literature (e.g., Piatti et al 2003;Bragaglia et al 2006;Carraro et al 2010;Lim et al 2014;Çakmak et al 2020;Abdelaziz et al 2020;Dias et al 2021) are shown in Figure 9 and Table 3. Our distances of OCs agree very well with those distances determined previously, with a negligible median offset of the relative differences in distance ΔD/D of −0.8%/−0.6% and a standard deviation value of 5.6%/3.4% for the APO/LM-LRGB samples.…”
Section: Validation Of Distance Estimatesmentioning
confidence: 74%
“…Our estimated value of color-excess in Gaia bands (E(BP − RP )) is 0.43 mag from the isochrones fitting to the CMD's. We have calculated the interstellar reddening (E(B − V )) as 0.34 mag using the transformation equations (E(B − V )= 0.785 E(BP − RP )) as taken from Abdelaziz et al (2020). Distance modulus (m − M G =12.51 mag) of IC 1434 provides the heliocentric distance as 3.2±0.1 kpc.…”
Section: Age and Distance Estimation Using Cmdmentioning
confidence: 99%
“…Stellar photometry is a basic tool to study the physical properties of young stellar systems Lim et al 2015a;Abdelaziz et al 2020. However, since most young open clusters are distributed in the Galactic plane, it is essential to discriminate cluster members from field interlopers to determine the reliable results.…”
Section: Introductionmentioning
confidence: 99%